How the Toxin got its Toxicity - Jackson, Timothy N. W.; Koludarov, Ivan (Frontiers in Pharmacology, 2020)
Venom systems are functional and ecological traits, typically used by one organism to subdue or deter another. A predominant subset of their constituent molecules – “toxins” – shares this ecological function and are therefore molecules that mediate interactions between organisms. Such molecules have been referred to as “exochemicals”. There has been debate within the field of toxinology concerning the evolutionary pathways leading to the “recruitment” of a gene product for a toxic role within venom. We review these discussions and the evidence interpreted in support of alternate pathways, along with many of the most popular models describing the origin of novel molecular functions in general. We note that such functions may arise with or without gene duplication occurring and are often the consequence of a gene product encountering a novel “environment”, i.e. a range of novel partners for molecular interaction. After stressing the distinction between “activity” and “function”, we describe in detail the results of a recent study which reconstructed the evolutionary history of a multigene family that has been recruited as a toxin and argue that these results indicate that a pluralistic approach to understanding the origin of novel functions is advantageous. This leads us to recommend that an expansive approach be taken to the definition of “neofunctionalization” – simply the origins of a novel molecular function by any process – and “recruitment” – the “weaponization” of a molecule via the acquisition of a toxic function in venom, by any process. Recruitment does not occur at the molecular level or even at the level of gene expression, but only when a confluence of factors results in the ecological deployment of a physiologically active molecule as a toxin. Subsequent to recruitment, the evolutionary regime of a gene family may shift into a more dynamic form of “birth-and-death”. Thus, recruitment leads to a form of “downwards causation”, in which a change at the ecological level at which whole organisms interact leads to a change in patterns of evolution at the genomic level.